2023
DOI: 10.1371/journal.pone.0288315
|View full text |Cite
|
Sign up to set email alerts
|

Does intellectual property protection promote green innovation in firms? A perspective on R&D spillovers and financing constraints

Xiaoyuan Gao,
Yixin Zhao

Abstract: Although the literature has assessed the impact of Intellectual property protection on urban innovation, there is still a gap in the assessment of the impact of green innovation at the firm level. This study constructs a multi-period differences-in-differences (DID) model using China’s Intellectual Property Demonstration Cities (IPDC) as a quasi-natural experiment to investigate the impact of IPDC on corporate green innovation. The findings indicate that (1) the IPDC program significantly stimulates corporate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Intellectual property protection stimulates knowledge sharing and innovation output [8][9][10], promotes technology progress and productivity improvement in firms [11]. Simultaneously, intellectual property protection will also reduce knowledge spillovers [12][13][14], strengthen the technological and market monopoly position of firms, and reduce productivity. Therefore, empirical research has found inconsistent conclusions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intellectual property protection stimulates knowledge sharing and innovation output [8][9][10], promotes technology progress and productivity improvement in firms [11]. Simultaneously, intellectual property protection will also reduce knowledge spillovers [12][13][14], strengthen the technological and market monopoly position of firms, and reduce productivity. Therefore, empirical research has found inconsistent conclusions.…”
Section: Literature Reviewmentioning
confidence: 99%